PDTM-06. ALK AMPLIFICATION AND REARRANGEMENTS ARE RECURRENT TARGETABLE EVENTS IN GLIOBLASTOMA. (5th November 2018) - Blandin, Anne-Florence; Graham, Maya; Ramkissoon, Shakti; Ramkissoon, Lori; Pelton, Kristine; Pages, Mélanie; Jones, Robert; Becker, Sarah; Watkinson, Fiona; Schoolcraft, Kathleen; Haemels, Veerle; Goumnerova, Liliana; et al.
Abstract: Anaplastic Lymphoma Kinase (ALK ) expression, rearrangements, and single nucleotide variants have been reported in several brain tumor types, but the significance and function of each aberration in adults and children have not been clearly established. To determine the degree to which ALK represents a relevant therapeutic target in gliomas, we first examined ALK expression using immunohistochemistry (IHC) in a panel of 148 adult GBM and 49 pediatric GBM/high grade gliomas. We identified high ALK expression was most frequent in pediatric gliomas (32%, 16/49, IHC score 2+ or 3+). Copy arrays/sequencing and FISH for the ALK locus revealed high level ALK amplification in 31% of ALK -expressing cases (5/16) but was a rare event in gliomas overall. Whole-genome sequencing and RNA sequencing identified novel and recurrent PPP1CB - ALK fusions in 43% of ALK -expressing pediatric GBM (7/16), suggesting IHC may be an efficient means of screening for ALK aberrations as in the identification of EML4-ALK lung cancer. All ALK - amplified cases harbored PPP1CB-ALK fusion but 2 PPP1CB-ALK cases were copy neutral. The phosphatase PPP1CB was fused in-frame to ALK at exon 20 with preservation of the ALK kinase domain and predicted to activate via the same mechanism as other ALK rearranged cancers. ALK fusion proteins promoted cell proliferation and constitutive kinase activity and upregulated STAT and AKT signaling pathways. However, expression of novel ALK missense mutations in NSCs did not promote proliferation. Administration of ALK inhibitor Crizotinib reduced tumor growth in a PDX GBM from a patient with a novel ALK fusion. This work validates amplification and rearrangement of ALK as a highly recurrent driver event and therapeutic target in GBM, particularly in young children where it may be the sole driver event.